Monodispersed Size-Controlled Gold Nanoparticles from Electrodeposited Aminoferrocenyl Dendrimer-Templates and Their Application as Efficient Hydrogen Peroxide Electrocatalyst. Issue 7 (1st January 2018) - Villena, Carlos; Punjabi, Divesh; Casado, Carmen M.; Alonso, Beatriz; Losada, José; Armada, M. Pilar García
Abstract : The main target of this work is the development of efficient hydrogen peroxide non-enzymatic sensors based on size-controlled gold nanoparticles from electrodeposited aminoferrocenyl dendrimer-templates. In this work we study the kinetics and electrochemistry of the modified electrodes as well as the kinetics and the analytical responses of them to both the oxidation and reduction of hydrogen peroxide via different processes related with the absence or presence of gold nanoparticles and their size. The best responses as non-enzymatic sensors were observed at 0.5 V with the largest nanoparticles, obtained from the first generation dendrimer-template, with two linear ranges (0.001–1.2 and 1.2–4.0 mM), sensitivities 249.5 and 185.6 μA/mM cm 2 and limit of detection of 0.07 μM; and at −0.2 V with the smallest ones, obtained from the fifth generation, with three linear ranges (0.001–2.0, 2.0–4.0 and 4.0–15.0 mM), sensitivities 172.1, 888.4 and 437.0 μA/mM cm 2 respectively, and limit of detection of 0.06 μM. The non-enzymatic peroxide sensors showed an interference-free behavior at −0.2 V.